Negotiating Marriage Beyond Traditional And Modern Contexts: An Interpretative Phenomenology Analysis Of Upper-Caste Women In Ngada - Theresia Avila Chastysima Daku; Jefri Setyawan (INJECT (Interdisciplinary Journal of Communication), 2025)
Cultural expectations for upper-caste women in Ngada society demand that they marry within their caste. This study opens a communicative space for women who have successfully negotiated traditional norms. It aims to understand how women negotiate marriage choices with their families and how social support and communication affect their decision-making processes. This qualitative study uses an interpretative phenomenological approach, employing semi-structured interviews with three upper-caste women who married men of lower-caste status. The findings show that cultural expectations to preserve social status through intra-caste marriage persist, placing pressure on women to relinquish autonomy in making marital decisions. However, open communication about personal choices and seeking family support allowed for the emergence of emotional, instrumental, and informational support that greatly helped women overcome social stigma and choose partners independently. The implications of this study underscore the importance of open family communication in supporting individual freedom in a partner.